Murine‐Derived Glioma Organoids and Cell Line Culture Systems. Issue 2 (6th February 2023) - Ayala‐Sarmiento, Alberto E.; Pacheco, David Rincon Fernandez; Breunig, Joshua J.
Abstract: Research models in cancer have greatly evolved in the last decade, with the advent of several new methods both in vitro and in vivo. While in vivo models remain the gold standard for preclinical studies, these methods present a series of disadvantages such as a high cost and long periods of time to produce results compared with in vitro models. We have previously developed a method named Mosaic Analysis by Dual Recombinase‐mediated cassette exchange (MADR) that generates autochthonous gliomas in immunocompetent mice through the transgenesis of personalized driver mutations, which highly mimic the spatial and temporal tumor development of their human counterparts. Due to the control of single‐copy expression of transgenes, it allows for comparing the visualization of tumor cells and non‐tumor cells. Here we describe a method to generate murine‐derived glioma organoids (MGOs) and cell line cultures from these murine models by physical and enzymatic methods for in vitro downstream applications. Tumor cells can be readily distinguished from non‐tumor cell populations, in both organoids and monolayer cell cultures, and isolated due to the use of personalized fluorescent reporter transgenes. © 2023 Wiley Periodicals LLC. Basic Protocol 1 : Generation of 3D murine‐derived glioma organoids Basic Protocol 2 : Generation of 2D glioma monolayer cell lines